The Semiotic Paradigm – a Transdisciplinary Approach to Sciences - Carac, Ioan S. (Acta Universitatis Danubius. Communicatio, 2022)
This essay deals with inter-, pluri- and transdisciplinarity, taking as a point of departure some studies written by scholars such as Eugenio Coseriu, Stéphane Lupasco, Basarab Nicolescu, Petru Ioan. Aware of the crisis encountered by modern epistemology, Ioan S. Cârâc states that semiotics can pilot the other sciences in the future. In order to choose a way that leads to studying reality as an unfragmented whole, one needs to switch the analytical mode of thinking, specific to traditional science, with the synthetical mode of thinking. In other terms, semiotics (the science of signs) could impose a transdisciplinary logical method which is meant to disentangle modern epistemology. Ioan S. Cârâc tries to prove that semiotics should be essentially a unitary and transdisciplinary theory and, consequently, he finds within the Romanian culture possible solutions for establishing such an integral semiotics: that is, Eugenio Coseriu’s integral linguistics, along with some theoretical ideas belonging to the logician Petru Ioan, who elaborated a hexadic model of the “semiotic situation”, envisaging semiotics as a syntax semantically and pragmatically justified.